Serial macromolecular crystallography at ALBA Synchrotron Light Source. Erratum. (16th May 2022) - Martin-Garcia, Jose M.; Botha, Sabine; Hu, Hao; Jernigan, Rebecca; Castellví, Albert; Lisova, Stella; Gil, Fernando; Calisto, Barbara; Crespo, Isidro; Roy-Chowdhury, Shatabdi; Grieco, Alice; Ketawala, Gihan; et al.
Abstract : A PDB code given in Table 2 of Martin‐Garcia et al. [ J. Synchrotron Rad. (2022). 29, 896–907 ] is corrected. Abstract : A revised version of Table 2 of Martin‐Garcia et al. [ J. Synchrotron Rad. (2022). 29, 896–907 ] is provided.